Identificação da curva de Phillips Novo Keynesiana para uma pequena economia aberta - Lima, Ricari Carolini Araújo de (2022)
This paper aimed to analyze the inflationary dynamics in Brazil, considering it as a small open economy and using robust estimation procedures for weak identification. The first approach consists of using predetermined variables as instruments, and the second one involves monetary shocks. In general terms, it was found that monetary shocks cannot identify the coefficients of the New Keynesian Phillips curve for a small open economy using Brazilian data. However, when using lagged instruments, the parameters were identified. In this approach, it was observed that variables related to Brazil’s open economy had a reduced influence in explaining current inflation with recent data. Nevertheless, it was noted that the exchange rate still plays an informative role regarding the behavior of marginal costs.